PENTINGKAH KUALITAS DAN KESEJAHTERAAN GURU BIOLOGI? - Abdul Rasyid Fakhrun Gani; Andi Basliahwanti Murti; Devi Alvionita (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2021)
Education is one of the important pillars in a country. Efforts to improve the quality of education must begin with improving the quality of teachers. This study aims to analyze the importance of teacher quality and welfare to promote biology learning in Indonesia. This research is conducted online by analyzing scientific journals and other articles to find the intended concept. The research was conducted qualitatively by collecting data, reducing data, presenting data, and drawing conclusions. The results of this study are the quality and welfare of teachers must be directly proportional. Improving the quality and welfare of teachers, facilitating all educational programs and providing supervision, evaluation and follow-up can have a major impact in the world of education. A well-qualified teacher can develop learning that supports students to face the challenges of the times. Teachers need to guarantee the quality of life and quality of work, so as to improve their quality to improve the quality of state education.